2009
DOI: 10.1002/ajmg.a.32941
|View full text |Cite
|
Sign up to set email alerts
|

A 1q42 deletion involving DISC1, DISC2, and TSNAX in an autism spectrum disorder

Abstract: Individuals with autism spectrum disorders have impairments in social, communicative, and behavior development that are often accompanied by abnormalities in cognitive functioning, learning, attention, and sensory processing. In this report, we describe a 3-year-old male child with an autism spectrum disorder who carries a 2Mb deletion of chromosome 1q42. Array comparative genome hybridization revealed that this deletion involves at least three genes-DISC1, DISC2, and TSNAX-which have been found to be associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…They found 477 insertional translocations with an incidence of approximately 2.1%, demonstrating that the frequency detected with array-CGH seems to be higher . This result is confirmed by some other recent studies which estimated the frequency of these rearrangements at the submicroscopic level by array-CGH [Bartsch et al, 2001;Williams et al, 2009;Crepel et al, 2010;Rigola et al, 2015;Morris et al, 2016;Wang et al, 2016].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…They found 477 insertional translocations with an incidence of approximately 2.1%, demonstrating that the frequency detected with array-CGH seems to be higher . This result is confirmed by some other recent studies which estimated the frequency of these rearrangements at the submicroscopic level by array-CGH [Bartsch et al, 2001;Williams et al, 2009;Crepel et al, 2010;Rigola et al, 2015;Morris et al, 2016;Wang et al, 2016].…”
supporting
confidence: 88%
“…Rearrangements of the region 1q42.13q43 are rare, with only 7 cases reported to date [Beemer et al, 1985;Bortotto et al, 1990;Kato et al, 2007;Williams et al, 2009;Crepel et al, 2010;Rigola et al, 2015;Wang et al, 2016]. The imbalances described are usually the result of inherited translocations involving other chromosomes, making difficult to establish a specific karyotype/phenotype correlation.…”
mentioning
confidence: 99%
“…Molecular analysis of the region involved in the present paracentric inversion (http://www.ncbi.nlm.nih.gov) showed that 11 of the 316 genes known in the inverted region as well as 4 genes of the 210 located in proximal regions (1q42.11-1q42.12 and 1q44) are associated with intellectual disability or with the central nervous system ( table 1 ). To data, at least 30 patients with chromosome deletions of 1q42q44 with mental retardation of variable severity, autism, neuropsychiatric disorders, microcephaly, and corpus callosum anomalies have been reported [Hill et al, 2007;Williams et al, 2009;Filges et al, 2010;Ballif et al, 2011;Dutta et al, 2011;Perrone et al, 2012;Nagamani et al, 2012;Petersen et al, 2013;Au et al, 2014;Poretti et al, 2014;Delabio et al, 2014;de Munnik et al, 2014;Gai et al, 2015]. These authors proposed some genes as excellent candidates because of their role in the developing central nervous system (DISC2, MTR, FMN2, and CHRM3) or their expression in brain tissue (FBXO28,LEFTY1,LEFTY2,PSEN2,DISC1,TSNAX,B3GALNT2,AKT3,RPS7P5,SDCCAG8,and ZBTB18) .…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of DISC genomic loci is linked to many psychiatric diseases schizophrenia, schizoaffective disorder, bipolar disorder, major depression, and autistic spectrum disorders (Chubb et al, 2008;Millar et al, 2000;Williams et al, 2009) differentially expressed between ESCs and differentiated neurons are related to schizophrenia (SZ), bipolar disorder (BD) and even autism spectrum disorders (ASD) (Lin et al, 2011). We have summarized several lncRNAs involved in diseases of the CNS and brain in Table 2.…”
Section: Disc2mentioning
confidence: 99%